2003
DOI: 10.1080/0962935031000134897
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression and release of interleukin‐8 induced by serum amyloid A in neutrophils and monocytes

Abstract: The acute phase response is a systemic reaction to inflammatory processes characterized by multiple physiological adaptations, including the hepatic synthesis of acute-phase proteins. In humans, serum amyloid A (SAA) is one of the most prominent of these proteins. Despite the huge increase of serum levels of SAA in inflammation, its biological role remains to be elucidated, even though SAA is undoubtedly active in neutrophils. In a previous study, we reported that SAA induces the release of tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 43 publications
5
51
0
5
Order By: Relevance
“…Previous studies have demonstrated that p38 MAPK inhibition attenuates chemotaxis [36][37][38][39] and superoxide generation [40], in addition to pro-inflammatory mediator generation [41][42][43] in blood neutrophils. The lack of activated p38 MAPK observed in lung neutrophils makes it unlikely that p38 MAPK inhibition would have any effect on chemotaxis and superoxide generation in lung neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that p38 MAPK inhibition attenuates chemotaxis [36][37][38][39] and superoxide generation [40], in addition to pro-inflammatory mediator generation [41][42][43] in blood neutrophils. The lack of activated p38 MAPK observed in lung neutrophils makes it unlikely that p38 MAPK inhibition would have any effect on chemotaxis and superoxide generation in lung neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of b 2 -adrenergic receptors may involve the release of a mediator that would impair chemotaxis. For example, it has been shown that IL-8, which is produced by neutrophils (Ribeiro et al, 2003), inhibits neutrophil chemotaxis, in vitro, towards a distant source of IL-8 . We observed that cell culture supernatants collected from isoprenaline-stimulated neutrophils initiated chemotaxis in neutrophils from both males and females.…”
Section: De Coupade Et Almentioning
confidence: 99%
“…In this respect, interleukin (IL)-8, tumour necrosis factor (TNF)-a and interleukin (IL)-1b are proinflammatory cytokines with a central role in inflammatory processes. IL-8 shows angiogenic, chemotactic and stimulatory activities toward blood cells, providing the recruitment of a great number of neutrophils and other immune cells to the inflammatory site and favouring the appearance of neovascularization [13,14]. TNF-a mediates the systemic effects of inflammation, such as fever, the hepatic release of acute phase proteins and haematopoiesis.…”
Section: Introductionmentioning
confidence: 99%